Samsara Architecture: Exploring Situation Awareness in Cloud Computing Management - Neves, Vilnei; Pilla, Maurício; Yamin, Adenauer; Pilla, Laércio (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2018: Anais do XIX Simpósio em Sistemas Computacionais de Alto Desempenho, 2018)
Issues related to energy consumption and its efficiency in large-scale computing environments have emerged as critical points in the development of modern computer systems. This article presents the Samsara architecture concept, which aims to manage energy efficient computational clouds. The architecture was developed exploring situation awareness strategies, operating autonomously and with minimal human intervention, essential aspects in massive data processing centers. Samsara has been implemented as one of the modules of the OpenStack cloud platform and considers the maximum allocation capacity of each physical machine, to consolidate the workloads. In the evaluations carried out with synthetic loads, reductions of up to 12.3% in the energy consumption in the managed computational infrastructure were achieved, demonstrating the potential of Samsara for the operation of computational clouds.